RETRACTED ARTICLE: Navigating the crossroads: cardiometabolic risks in cancer survivorship – a comprehensive review - Arif Albulushi; Aisha Al Balushi; Muhhamed Shahzad; Ismail Al Bulushi; Hatim Al Lawati (Cardio-Oncology)
Abstract The landscape of cancer survivorship is increasingly populated by individuals facing a spectrum of cardiometabolic risks, attributed to both their oncological history and treatment regimens. This manuscript synthesizes findings from various studies, highlighting the prevalence of traditional risk factors—hypertension, dyslipidemia, diabetes—as well as emergent concerns like obesity and metabolic syndrome among survivors. The impact of demographic variables, specific cancer types, and treatment modalities on cardiometabolic health is explored. Through a lens of multidisciplinary management and future research directives, we advocate for an integrative approach to cardiometabolic health in cancer survivors, aiming to ensure their victory over cancer extends into long-term well-being. Furthermore, we discuss the outcome implications of these cardiometabolic risk factors on cardiovascular disease development, future cardiovascular events, and overall survival, supported by studies showing improved outcomes through exercise and risk factor control.